Associations of MTHFR gene polymorphism with lipid metabolism and risk of cerebral infarction in the Northwest Han Chinese population - Guan, Dong; Ji, Yichun; Lu, Xiaoyun; Feng, Weiyi; Ma, Wenbing (Frontiers in Neurology, 2023)
Objective: The Methylenetetrahydrofolate reductase (MTHFR) genetic variation may contribute to the development of Cerebral Infarction (CI), however, the results were inconsistent in different population studies even in the Chinese population. The aim of this study is to analyze the effect of MTHFR gene polymorphisms on serum lipid and homocysteine levels in the Northwest Chinese Han population with CI. Patients and Methods: 521 CI patients and 524 non-CI controls were enrolled in the study. Polymerase chain reaction and hybridization were utilized to determine the MTHFR gene polymorphisms. Multivariate logistic regression analysis were used to assess the associations of the MTHFR gene polymorphism with the risk of CI. Results: The present study found that the TT genotype and T allele frequency in the CI patients were markedly higher than in controls. After stratifying our data by sex and age, we detected that the TT genotype and T allele showed a statistically significant higher frequency in different ages participants and male patients, but no statistically significant differences between female patients and female controls. CI patients and control participants with CT/TT carriers had significantly higher homocysteine (Hcy) levels than those with CC carriers. The CT/TT carriers showed significantly lower high-density lipoprotein cholesterol (HDL-C) and ApoA-I levels as compared with CC carriers in CI patients, but there was no significant difference for control subjects. Multivariable logistic regression analysis showed that drinking, smoking, diabetes mellitus, Hcy, direct bilirubin (DB), indirect bilirubin (IB), ApoA-I, total protein (TP) and TT genotype were significant independent risk factors for CI. Conclusions: It was suggested that TT genotype MTHFR C677T gene polymorphism associated with hyperhomocysteinaemia (HHcy) might be of great clinical significance to identify new biomarkers for CI and individualized preventive and therapeutic strategies.